The roles of public relations practitioner in social media during Covid-19 / Nazreen Nasriq Samsi ... [et al.] - Samsi, Nazreen Nasriq; Abdul Rashid, Aiman Syahmi; Mohd Syukri Adli, Siti Hajar; Mohd Zainal, Maisarah; Ramlee, Rayhan Ereeza (Faculty of Communication & Media Studies, 2021)
The Public Relations Practitioner/Officer (PRO) or Corporate Communications (Corp Comm) uses various means of communication to create successful two-way communications between the business and other groups of people. It focuses on bringing the public and a company together in order to display a common understanding or image. PRO professionals use a wide variety of media to establish and maintain positive relations between the hiring agency and its customers by organized marketing promotions and PR events. The objective of this research is to identify the roles of public relations practitioner in social media during COVID-19 in which the challenges faced by PRO in the current COVID-19 pandemic situation, the social media is important in doing PRO task, how they use social media as a part of PRO working routine and are PRO highly dependent to social media for their company through the use of qualitative research, which is an interview to understand and describe the social phenomenon. Lastly, the researchers analysed the data by using thematic analysis. The findings of this research come out that the answer has somehow given from the online interview session in many types of platform such as Google Meet, WhatsApp Video Call and Zoom Meeting which effect on daily life.